Antithrombin III Determination by Rate (Kinetic) Nephelometry - Balla, G; Misz, M; Karmazsin, L; Rák, K (Thrombosis and Haemostasis, 1984)
Rate nephelometry immunological antithrombin III determination was elaborated with Beckman Immunochemistry System. The measuring can be carried out within 60 sec from 20 μl plasma. The results show a close correlation with those of gained by the radial immunodiffusion method (r = 0.91) and by Coatest (Kabi-Ortho) (r = 0.77). Both laser-nephelometric and usual non-nephelometric anti-antithrombin III serum (Behring) may be applied.
Keywords: Antithrombin III (AT-III); Rate nephelometry